2014
DOI: 10.1163/15685403-00003338
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of the genus Typhlocypris Vejdovský, 1882 (Ostracoda, Candonidae)

Abstract: The taxonomy of the genus Vejdovský, 1882 is reviewed. New morphological information on (Vejdovský, 1882), the type species of the genus, is provided, and a new reference material is presented. The generic diagnosis is emended with details derived from the developmental trajectory of the valves, from the juvenile stage A-3 to the adult. Those criteria clearly differentiate from the related genus Kaufmann, 1900. As here redefined, is a phylogentic lineage of the subfamily Candoninae containing extant species pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The three new species of Pseudocandona described herein and Pseudocandona tenuirostris all belong to the rostrata-group of the genus, characterized by a similar carapace shape and a group of three+one+beta setae on the inner edge of the second segment of the mandibular palp (Meisch 2000). In contrast, P. pratensis belongs to the compressa-group, while the position of P. abei is unclear, not fitting into the recent definition of Typhlocypris, nor the compressa-and rostrata-groups, which are Pseudocandona sensu stricto (Namiotko et al 2014). All of the rostrata-group species in Japan and P. abei are currently only known from Japan, and are potentially endemic, while the sole representative of the compressa-group in Japan, P. pratensis, is known in Korea (albeit only by two female specimens) (Karanovic 2013), and Europe (see review of distribution in Meisch 2000).…”
Section: Discussionmentioning
confidence: 91%
“…The three new species of Pseudocandona described herein and Pseudocandona tenuirostris all belong to the rostrata-group of the genus, characterized by a similar carapace shape and a group of three+one+beta setae on the inner edge of the second segment of the mandibular palp (Meisch 2000). In contrast, P. pratensis belongs to the compressa-group, while the position of P. abei is unclear, not fitting into the recent definition of Typhlocypris, nor the compressa-and rostrata-groups, which are Pseudocandona sensu stricto (Namiotko et al 2014). All of the rostrata-group species in Japan and P. abei are currently only known from Japan, and are potentially endemic, while the sole representative of the compressa-group in Japan, P. pratensis, is known in Korea (albeit only by two female specimens) (Karanovic 2013), and Europe (see review of distribution in Meisch 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Meisch (2000) foreshadowed a solution, by suggesting that the eremita-group of Pseudocandona has a clearly distinct morphology, sufficient to consider it a genus separate from Pseudocandona. Namiotko et al (2014) meanwhile have indeed reinstated Typhlocypris as a separate genus for the eremita-lineage, while Danielopol et al (2012) have created the genus Marmocandona for the zschokkeispecies group in Pseudocandona. We follow this position and maintain all other species groups for the time being within Pseudocandona, although, as foreshadowed by Danielopol (1978), at least the Pseudocandona species of the Siberian Lake Baikal will eventually have to be transferred to a new genus.…”
Section: Taxonomy Of Pseudocandona and Typhlocyprismentioning
confidence: 99%
“…For a full discussion on the taxonomic and nomenclatorial history of Typhlocypris and Pseudocandona, see Namiotko et al (2014 Broodbakker (1983) described four species in the genus Pseudocandona from the West Indies and also transferred the Columbian species Candona annae Mehes, 1914 to this genus, albeit implicitly. Mehes (1914, fig.…”
Section: Taxonomy Of Pseudocandona and Typhlocyprismentioning
confidence: 99%
“…Among the 3 subfamilies (Cyclocypridinae Kaufmann, 1900, Candoninae Kaufmann, 1900, and Paracypridinae Sars, 1923 of the family, Candoninae is the largest group with about 42 genera and more than 500 species distributed worldwide (Külköylüoğlu et al 2011;Martens and Savatenalinton 2011;Karanovic 2012). Although most species are known from epigean waters, studies have shown that hypogean candonid ostracods are unique and diverse (Schornikov 1969;Danielopol 1978;Karanovic and Pesce 2000;Danielopol et al 2011;Smith 2011), and that their diversity is underestimated (Külköylüoğlu et al 2011, in review;Namiotko et al 2014). Because groundwater ostracods show strong adaptive characteristics, some species and genera are also known to be groundwater endemics; for instance, Phreatocandona Danielopol, 1973 andTrajancandona Karanovic, 1999 were described from ground waters of Romania and Montenegro, respectively (Danielopol 1978;Karanovic 1999).…”
Section: Introductionmentioning
confidence: 99%